Linguistic skills in the academic field: Profiles of acquisition, assessment and use of English by scientific researchers in Argentina - Gallardo, Jorge Osvaldo (2022)
The aim of this article is to discuss the process of acquisition and use of English by scientific researchers whose mother language is Spanish. The data has been generated by both a survey (N = 2.390) and analysis of curriculum vitae (N = 4.638) of researchers at  Conicet (Argentina). Different English learning profiles have been identified indicating there is a connection  between the acquisition trajectory and the social origin of researchers.  However, the academic use of the language is highly determined by the field in which it is applied. Researchers of all scientific areas have advanced capacities in English. But these  capacities are mostly applied by stem researchers, particularly the writing skill.